Predictive factors of Status Epilepticus and its recurrence in patients with adult–onset seizures: A multicenter, long follow–up cohort study. (October 2021) - Gasparini, Sara; Ferlazzo, Edoardo; Gigli, Gianluigi; Pauletto, Giada; Nilo, Annacarmen; Lettieri, Christian; Bilo, Leonilda; Labate, Angelo; Fortunato, Francesco; Varrasi, Claudia; Cantello, Roberto; D'Aniello, Alfredo; et al.
Highlights: This cohort study analyzed predictors of occurrence and recurrence of SE in a large sample. SE occurrence was linked to advanced age, female sex, and definite etiology. SE recurrence was about 20%. Abstract: Purpose: Status epilepticus (SE) is associated with high morbidity and mortality. This multicenter retrospective cohort study aims to identify the factors associated with the occurrence of SE and the predictors of its recurrence in patients with adult–onset seizures. Methods: We retrospectively analyzed data of 1115 patients with seizure onset>18 years, observed from 1983 to 2020 in 7 Italian Centers (median follow–up 2.1 years). Data were collected from the databases of the Centers. Patients with SE were consecutively recruited, and patients without SE history were randomly selected in a 2:1 ratio. To assess determinants of SE, different clinical–demographic variables were evaluated and included in univariate and multivariate logistic regression model. Results: Three hundred forty–seven patients had a SE history, whereas the remaining 768 patients had either isolated seizures or epilepsy without SE history. The occurrence of SE was independently associated with increasing age at onset of disease (OR 1.02, 95% CI 1.01––1.03, p <0.001), female sex (OR 1.39, 95% CI 1.05––1.83, p =0.02) and known etiology (OR 3.58, 95% CI 2.61––4.93, p <0.001). SE recurred in 21% of patients with adult–onset SE and recurrence was associated with increasing number of anti–seizure medications taken at last follow–up (OR 1.88, 95% CI 1.31––2.71, p <0.001). Conclusions: In patients with adult–onset seizures, SE occurrence is associated with known etiologies, advanced age and female sex. Patients with recurrent SE are likely to have a refractory epilepsy, deserving careful treatment to prevent potentially fatal events.